2012
DOI: 10.1002/jmv.23231
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and epidemiology of astrovirus, bocavirus, and sapovirus in Italian children admitted to hospital with acute gastroenteritis, 2008–2009

Abstract: Although a number of enteric viruses have been identified in children with acute gastroenteritis, the majority of cases of gastroenteritis remain undiagnosed. In order to provide more insights into the epidemiology of enteric viruses that are not included usually in routine diagnostic tests, cases of childhood sporadic gastroenteritis of unknown etiology requiring hospital admission in Parma, Italy, during 2008-2009, were screened for astrovirus (AstV), sapovirus (SaV), and bocavirus (BoV). The stools of 712 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
37
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 63 publications
5
37
1
Order By: Relevance
“…Epidemiological investigations for HAstVs worldwide have shown that type-1 HAstV is predominant, while the prevalence of other HAstVs can vary markedly (De Grazia et al, 2011;Medici et al, 2012 Gabbay et al, 2007;Guix et al, 2002;Mustafa et al, 2000;Victoria et al, 2007). Interestingly, type-4 HAstV, along with type-8 HAstV, seems to be associated with infection of older children and with longer duration of diarrhoea (>7 days) (Guix et al, 2002;Silva et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological investigations for HAstVs worldwide have shown that type-1 HAstV is predominant, while the prevalence of other HAstVs can vary markedly (De Grazia et al, 2011;Medici et al, 2012 Gabbay et al, 2007;Guix et al, 2002;Mustafa et al, 2000;Victoria et al, 2007). Interestingly, type-4 HAstV, along with type-8 HAstV, seems to be associated with infection of older children and with longer duration of diarrhoea (>7 days) (Guix et al, 2002;Silva et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Surveillance studies for HAstV in Italy identified the circulation of type-4 HAstV strains in 2002 (De Grazia et al, 2011) and again in 2008(De Grazia et al, 2012Medici et al, 2012). Based on a small sequence generated by the diagnostic primers Mon269-Mon270 (Noel et al, 1995) …”
Section: Introductionmentioning
confidence: 99%
“…L13745), the 2002 Italian HAstV-2 strains were clearly distinguishable phylogenetically from type 2a and type 2b strains, and they were classified as lineage 2c, along with a number of other strains detected worldwide since the mid-1990s (5). In a similar fashion, in 2009 a novel lineage, 2d, was identified (15). In order to investigate better the extent of the genetic heterogeneity observed in HAstV-2 strains, a 3.2-kb portion at the 3= end of the genome, encompassing an ϳ740-nt-long portion at the 3= end of ORF1b, the full-length ORF2 (2,400 nt), and the 3= untranslated region (3= UTR) (82 nt), was sequenced for two representative strains, ITA/2002/PA65R/ type2c (accession no.…”
mentioning
confidence: 80%
“…On the basis of the capsid protein precursor, HAstVs are classified genetically and antigenically into eight types (HAstV-1 to -8) (18). The predominant types appear to vary seasonally and geographically (3,5,10,12,15,23,24), although the relevance of this genetic and antigenic heterogeneity and these temporal and geographical fluctuations is unclear. Epidemiological investigations of HAstVs worldwide have shown that HAstV-1 is predominant, while the prevalence of HAstV-2 can vary markedly (1,5,13,15,21), reaching epidemiological relevance in some geographical settings and seasons (4,9,11,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation